Coconut wall tiles (COWAT) / Muhammad Irfan Ibrahim and Noor Azam Yahaya - Ibrahim, Muhammad Irfan; Yahaya, Noor Azam (2023)
Malaysia, like other developing countries, is seeing a surge in garbage creation and challenges connected with trash management. Clearly, the best strategy to reduce environmental effect is either to reduce trash generation or ensure that garbage is recycled, composted, or repurposed. Every day, approximately 30,000 tonnes of municipal solid trash are generated, accounting for 83% of the total waste production in the country, including agricultural wastes like coconut waste. Approximately 95% of the total trash is disposed of in landfills. The waste is produced from many parts of the coconut, including the husk, kernel, and flesh. There are even several studies conducted to assess the environmental effect of the ceramic sector. This research examines the influence of various characteristics such as sintering, smoke, and CO2 emissions.